2019
DOI: 10.1155/2019/4134260
|View full text |Cite
|
Sign up to set email alerts
|

Cone Beam Computed Tomography-Based Anatomical Assessment of the Olfactory Fossa

Abstract: This study aimed to investigate the olfactory fossa according to the Keros classification using cone beam computed tomography. This cross-sectional study analysed cone beam computed tomography images selected from a database belonging to a radiology centre. The scans of 174 healthy patients were analysed by using the Xoran software. Gender, age, and side were correlated with the Keros classification. The mean age of the 174 patients was 45.3 years. The most prevalent Keros classification was type II (65.52%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
4
10
2
Order By: Relevance
“…In our study, the most common were Keros type II (71.9%), followed by Keros type I (17.8%), Keros type III (10.3%). While a few studies reported the most common Keros type I [1,2,7,20,21], most studies were the most common type II [3][4][5]8,[13][14][15][17][18][19][22][23][24][25][26][27][28], consistent with our study. The distributions according to the Keros classification in the studies conducted in the Turkish population are presented in Table 6.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, the most common were Keros type II (71.9%), followed by Keros type I (17.8%), Keros type III (10.3%). While a few studies reported the most common Keros type I [1,2,7,20,21], most studies were the most common type II [3][4][5]8,[13][14][15][17][18][19][22][23][24][25][26][27][28], consistent with our study. The distributions according to the Keros classification in the studies conducted in the Turkish population are presented in Table 6.…”
Section: Discussionsupporting
confidence: 90%
“…The mean widths of OF and CP were statistically significant in our study. Unlike other studies, in our study, the mean CP depth was statistically significant according to the side [1,13,16]. The mean CP depth on the left was greater than the right.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…There was also no significant difference between sex and age and the depths of the right and left-sided olfactory fossa. [29] Yenigun et al [13] developed a new classification in addition to the Keros classification for the ethmoid roof based on Souza et al [21] 400 26.3 73.3 0.5 Jang et al [22] 205 30.5 69.5 none Anderhuber et al [19] 272 14.2 70.6 15.2 Nitinavakarn et al [18] 88 11.9 68.8 19.3 Adeel et al [17] 77 29.9 49.4 20.8 Basak et al [20] 64 9 53 38 Babu et al [9] 1200 visualization of the anterior ethmoidal artery, analyzing its relationship with neighboring structures in coronal, axial and sagittal CT images, evaluating its relationship with the ethmoid roof. The Keros classification used to measure lateral depth has been modified to measure the anteroposterior length of the cribriform plate on the ethmoid roof.…”
Section: Discussionmentioning
confidence: 99%
“…Asymmetry in the depth of the cribriform plate was seen in 33 [1,3,9,13,25,30]. No significant difference is reported in the distribution of Keros type between the left and right sides in some studies [12,13,24].…”
Section: Discussionmentioning
confidence: 94%